Pengaruh Kualitas Pelayanan Penanganan Covid-19 Terhadap Kepuasan Pengguna Jasa Angkutan Udara Pada Maskapai Garuda Indonesia di Bandar Udara Juanda Sidoarjo - Refalda Jeans Bagtira; Nanik Riananditasari (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to determine partially and simultaneously the influence of the service quality dimension on the satisfaction of Garuda Indonesia airline service users at Juanda Airport Sidoarjo. This research uses quantitative methods. Data collection techniques by distributing questionnaires with a sample of 196 respondents. Service quality has a significant positive impact on passenger satisfaction on Garuda Indonesia airlines simultaneously. However, there are only four variables that have a positive and significant influence on the satisfaction of air transportation service users partially, namely tangible, reliability, assurance, and empathy, while one other variable, namely responsiveness, has no significant effect. The influence of the service quality variable that is more dominant on passenger satisfaction is reliability. The results showed that 68.6% of Garuda Indonesia's customer satisfaction was influenced by service quality.